If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 5y) * dx + (5x + 6y) * dy = 0 Reorder the terms for easier multiplication: dx(4x + 5y) + (5x + 6y) * dy = 0 (4x * dx + 5y * dx) + (5x + 6y) * dy = 0 Reorder the terms: (5dxy + 4dx2) + (5x + 6y) * dy = 0 (5dxy + 4dx2) + (5x + 6y) * dy = 0 Reorder the terms for easier multiplication: 5dxy + 4dx2 + dy(5x + 6y) = 0 5dxy + 4dx2 + (5x * dy + 6y * dy) = 0 5dxy + 4dx2 + (5dxy + 6dy2) = 0 Reorder the terms: 5dxy + 5dxy + 4dx2 + 6dy2 = 0 Combine like terms: 5dxy + 5dxy = 10dxy 10dxy + 4dx2 + 6dy2 = 0 Solving 10dxy + 4dx2 + 6dy2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '2d'. 2d(5xy + 2x2 + 3y2) = 0 Factor a trinomial. 2d((x + y)(2x + 3y)) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0Subproblem 2
Set the factor '(x + y)' equal to zero and attempt to solve: Simplifying x + y = 0 Solving x + y = 0 Move all terms containing d to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x + y = 0 + -1x Combine like terms: x + -1x = 0 0 + y = 0 + -1x y = 0 + -1x Remove the zero: y = -1x Add '-1y' to each side of the equation. y + -1y = -1x + -1y Combine like terms: y + -1y = 0 0 = -1x + -1y Simplifying 0 = -1x + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 3
Set the factor '(2x + 3y)' equal to zero and attempt to solve: Simplifying 2x + 3y = 0 Solving 2x + 3y = 0 Move all terms containing d to the left, all other terms to the right. Add '-2x' to each side of the equation. 2x + -2x + 3y = 0 + -2x Combine like terms: 2x + -2x = 0 0 + 3y = 0 + -2x 3y = 0 + -2x Remove the zero: 3y = -2x Add '-3y' to each side of the equation. 3y + -3y = -2x + -3y Combine like terms: 3y + -3y = 0 0 = -2x + -3y Simplifying 0 = -2x + -3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
d = {0}
| 18x+63=27x-72 | | 25y^2+40y+16=28 | | 3(x)+2=11 | | 8a+8=24 | | 7-11z=-114 | | 40x+1.5=25x+3 | | 8y-y-3y= | | f(x)=6x^3-5x^2+6x+5 | | 2x+x+8=7 | | ln*15-ln*x=5 | | 700+.5x=737 | | 3(4y-5)=60 | | 0.6x^2+0.7x+1=0 | | 4h+2h+3h-9h+3h-2=19 | | 700+.5=737 | | 2x-x+8=7 | | y=ax^2-b | | 3c^2-8c+4=0 | | x^2-8y+6x+25+y^2=0 | | 4=3x-18 | | 66-(7x+6)=7(x+2)+x | | 12x-x^2=12.8 | | 22r+18=32r-24 | | a+4a-21=0 | | x^2+49x-380=0 | | -4v+6v=-16 | | 4x^4+2x^3-39x^2+43x-10=0 | | 6x-8x+10=87-21+10x | | x-(-11)=18 | | -7(2t+3)=-35 | | s*4-46=-2 | | 49x+1.5=25x+3 |